Robotic Partial Nephrectomy with the Da Vinci Xi. (9th February 2016) - Kallingal, George J. S.; Swain, Sanjaya; Darwiche, Fadi; Punnen, Sanoj; Manoharan, Murugesan; Gonzalgo, Mark L.; Parekh, Dipen J.
Abstract : Purpose. The surgical expertise to perform robotic partial nephrectomy is heavily dependent on technology. The Da Vinci Xi (XI) is the latest robotic surgical platform with significant advancements compared to its predecessor. We describe our operative technique and experience with the XI system for robotic partial nephrectomy (RPN). Materials and Methods. Patients with clinical T1 renal masses were offered RPN with the XI. We used laser targeting, autopositioning, and a novel "in-line" port placement to perform RPN. Results. 15 patients underwent RPN with the XI. There were no intraoperative complications and no operative conversions. Mean console time was 101.3 minutes (range 44–176 minutes). Mean ischemia time was 17.5 minutes and estimated blood loss was 120 mLs. 12 of 15 patients had renal cell carcinoma. Two patients had oncocytoma and one had benign cystic disease. All patients had negative surgical margins and pathologic T1 disease. Two postoperative complications were encountered, including one patient who developed a pseudoaneurysm and one readmitted for presumed urinary tract infection. Conclusions. RPN with the XI system can be safely performed. Combining our surgical technique with the technological advancements on the XI offers patients acceptable pathologic and perioperative outcomes.